Account of Multilayered Ground for Calculation of Electromagnetic Parameters of Single Infinitely Long Rod-Shaped Electrodes at Alternating Current Flowing - Е. A. Dziaruhina (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The approximate equations considering multilayered ground and two-layer rod structure are proposed for calculation of electromagnetic parameters of single infinitely long electrode rods at power frequency current flowing. The paper presents results of parameters’ calculation for steel and coppered steel electrodes in two-layer ground.